Cegah Masalah Gizi Anak dengan Sosialisasi Pemberian Makanan Bayi dan Anak: Prevent Child Nutrition Problems with Infant and Young Child Feeding Socialization - Widaryanti, Rahayu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Community service activities aim to provide knowledge to mothers about infant and child feeding to prevent child nutrition problems. This community service activity was held at the meeting hall of Maguwoharjo village residents, Depok, Sleman, DI Yogyakarta. Before the socialization, respondents filled the pretest first and after the socialization filled the post-test. Data processing is done by Paired Sample t-Test. Through this program, community knowledge about infant and child feeding can be increased.